Potential Applications of Ultrasonic Sensor (International Journal of Engineering and Computer Science, 2017)
An ultrasonic sensor HC-SR04 uses ultrasonic waves to detect various objects. The operation of this ultrasonic sensor is not obstructed by sunlight or black material, so regardless of the lighting conditions it is able to work properly. This property makes it useful in number of applications. This sensor is used to make an Obstacle Sensing Robot (OSR) which when detects the presence of an object while working, is able to avoid collision with that object and change its path automatically. Various complimenting materials have been used to make the robot communicate with all its parts or components and to make it run. Further, after successful completion of obstacle sensing robot, a Maze Solving Robot (MSR) with the same hardware was implemented. It is capable to solve mazes and come out of mazes on its own without any external help.